Ibn Khaldun's Production Ethics and Islamic MSME Market Supply: A Civilizational Perspective - Rosidah Rosidah; Nur Ela; Deni Prastiono; Sri Rokhlinasari; Alvien Septian Haerisma (Politeknik Siber Cerdika Internasional, 2026)
Background: The low halal certification rate among Indonesian MSMEs, with fewer than 10% of 64 million business units certified halal, and the sharia economic literacy rate of only 9.14%, indicate a weak internalization of Islamic production ethics in market offerings. Meanwhile, Ibn Khaldun’s thought, which contains strong values of Islamic production ethics, has not been sufficiently explored as a conceptual basis for strengthening Indonesian Islamic MSMEs. Objective: This study aims to analyze Ibn Khaldun’s concept of Islamic production ethics, examine its relevance to Islamic market offerings, and describe its implications for strengthening Indonesian sharia-compliant MSMEs. Method: This study employs qualitative library research with a historical-analytical approach. It systematically examines Ibn Khaldun’s ethical production thought through Muqaddimah as the primary source and relevant classical and contemporary Islamic economic literature as secondary sources, then contextualizes the findings within Indonesian sharia MSMEs. Results: The findings show that Ibn Khaldun’s production ethics is centered on ‘umran, which integrates labor value, ‘asabiyyah or social solidarity, justice, ethical efficiency, and civilizational sustainability. This study constructs a five-principle operational framework for Islamic production ethics applicable to Indonesian halal MSME market supply. Conclusion: Integrating ‘umran and ‘asabiyyah into MSME production orientation may address the dualism between Islamic identity and profit-driven conventional business practices.